A Systematic Review of Algorithms with Linear-time Behaviour to Generate Delaunay and Voronoi Tessellations - Sanderson L. Gonzaga de Oliveira (2014)
Triangulations and tetrahedrizations are important geometrical discretization procedures applied to several areas, such as the reconstruction of surfaces and data visualization. Delaunay and Voronoi tessellations are discretization structures of domains with desirable geometrical properties. In this work, a systematic review of algorithms with linear-time behaviour to generate 2D/3D Delaunay and/or Voronoi tessellations is presented.